Republic of Tajikistan : 2015 Article IV Consultation-Press Release and Staff Report. (IMF Staff Country Reports; Country Report ;, 2021)
Growth has been strong and poverty has fallen in the past decade, though Tajikistan faces rising vulnerabilities. Growth is now softening and the external position has weakened dramatically as remittances have fallen with the sharp slowdown in Russia and earnings from cotton and aluminum exports have dropped due to global market developments. The exchange rate is under pressure and international reserves are thin. The fiscal position has been near balance in recent years and debt has been kept low, while fiscal space is becoming limited by rising debt service and contingent liabilities.